2010
DOI: 10.1007/s12199-010-0149-y
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of influenza virus infectivity on the surfaces of personal protective equipment and clothing used in healthcare settings

Abstract: Objectives The maintenance of infectivity of influenza viruses on the surfaces of personal protective equipment and clothing is an important factor in terms of controlling viral cross-infection in the environment and preventing contact infection. The aim of this study was to determine if laboratory-grown influenza A (H1N1) virus maintained infectivity on the surfaces of personal protective equipment and clothing used in healthcare settings. Methods Influenza A virus (0.5 mL) was deposited on the surface of a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 21 publications
2
66
0
Order By: Relevance
“…However, the hydrophobic fabrics gave a much higher virus recovery than hydrophilic Nylon, which agrees with the work of Sakaguchi et al 15. The AIV suspension formed droplets when applied to hydrophobic PP and PET surfaces with a small contact area between the virus and fibers while it easily spread and soaked into the Nylon fabrics with a much larger contact area and a higher probability for virus adsorption onto the fibers, consequently lowering the recovery efficiency.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the hydrophobic fabrics gave a much higher virus recovery than hydrophilic Nylon, which agrees with the work of Sakaguchi et al 15. The AIV suspension formed droplets when applied to hydrophobic PP and PET surfaces with a small contact area between the virus and fibers while it easily spread and soaked into the Nylon fabrics with a much larger contact area and a higher probability for virus adsorption onto the fibers, consequently lowering the recovery efficiency.…”
Section: Discussionsupporting
confidence: 90%
“…The virus could be easily transferred from contaminated PPE to the skin when the PPE is removed from healthcare workers,10 which may greatly increase the risk of contact transmission. It has also been documented that influenza virus can survive on a wide variety of surfaces including non‐woven fabrics 11, 12, 13, 14, 15…”
Section: Introductionmentioning
confidence: 99%
“…Control of viral contamination is important to prevent nosocomial transmission. Respiratory and enteric viruses have been reported to survive for days on surfaces, and viral infections are due to transfer from these surfaces to susceptible persons [12][13][14]. IFV and NoV can be transmitted by direct and indirect contact with contaminated surfaces and/or aerosol and is linked to the outbreaks in hospitals and long-term care facilities [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Methods previously used to recover influenza virus from environmental surfaces included a premoistened swab (15)(16)(17), surface rinsing (18), or a combination of residual liquid and a premoistened swab (19). To date, no recommended, standardized, or validated guidelines that describe the best methodology for recovery of viruses from any type of environmental surface are available.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of persistence on environmental surfaces have found that various strains of influenza A (H1N1) virus remained infectious on SS surfaces for approximately 24 h but no longer than 72 h (15)(16)(17)(18)(19). In this study, we evaluated the persistence and infectivity of two influenza A (H1N1) virus strains, A/New Caledonia/20/1999 (A/NC-H1N1) and A/Brisbane/59/2007 (A/Br-H1N1), in three different substrate matrices (viral medium, 2% fetal bovine serum [FBS], and 5 mg/ml mucin) on SS surfaces stored for various times up to 7 days under a range of absolute humidity conditions.…”
mentioning
confidence: 99%